2013
DOI: 10.1007/s00280-012-2030-8
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled study to evaluate the effect of repeated oral doses of pazopanib on cardiac conduction in patients with solid tumors

Abstract: Purpose As tyrosine kinase inhibitors have been associated with cardiotoxicity, we evaluated the effect of pazopanib, an inhibitor of vascular endothelial growth factor receptor, platelet-derived growth factor receptor, and c-Kit, on electrocardiographic parameters in patients with cancer. Methods This double-blind, placebo-controlled, parallel-group study randomized patients (N = 96) to moxifloxacin (positive control) or placebo on Day 1 followed by pazopanib or placebo 800 mg/day (fasted) on Days 2–8 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 11 publications
(12 reference statements)
0
24
0
Order By: Relevance
“…QTc prolongation was common (37%) in patients with hepatic impairment treated with bosutinib,10 but this was not seen in other smaller studies 11, 12. QTc prolongation was infrequent or absent with afatinib, crizotinib, ceritinib, dovitinib, imatinib, lapatinib, lenvatinib, nintedanib, pazopanib, and ponatinib 9, 14, 16, 17, 19, 24, 26, 27, 29, 30, 31, 32, 33, 35, 36, 38, 39, 72, 78, 81, 161, 162, 163, 164…”
Section: Resultsmentioning
confidence: 77%
“…QTc prolongation was common (37%) in patients with hepatic impairment treated with bosutinib,10 but this was not seen in other smaller studies 11, 12. QTc prolongation was infrequent or absent with afatinib, crizotinib, ceritinib, dovitinib, imatinib, lapatinib, lenvatinib, nintedanib, pazopanib, and ponatinib 9, 14, 16, 17, 19, 24, 26, 27, 29, 30, 31, 32, 33, 35, 36, 38, 39, 72, 78, 81, 161, 162, 163, 164…”
Section: Resultsmentioning
confidence: 77%
“…In phase II clinical trials, the mean increase in systolic BP seen with fostamatinib is approximately 5 mmHg in patients with rheumatoid arthritis (Weinblatt et al ., ; Genovese et al ., ). However, other VEGFR2 inhibitors show much greater increases in BP in the clinic (value in brackets refer to the mean mmHg increase in systolic BP): cediranib (19, Robinson et al ., ), pazopanib (18, Heath et al ., ), sorafenib (21, Veronese et al ., ), sunitinib (25, Eechoute et al ., ) and vandetanib (12, Mayer et al ., ). Therefore, the comparatively lower increase in BP seen with fostamatinib may reflect the lower inhibition of VEGFR2 at therapeutic levels.…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of the 23 articles showed that the year of publication ranged between 1985 and 2015, with thirteen published in the United States (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) , seven in England (24)(25)(26)(27)(28)(29)(30) and three in other European countries (31)(32)(33) . Regarding the levels of evidence, the following distribution was observed: one level I (27) , seven level II (15,17,20,22,(28)(29)31) , six level III (13,(18)(19)21,23,30) , and nine level IV (11)(12)14,16,24,26,(32)(33) .…”
Section: Resultsmentioning
confidence: 99%